ПЕДАГОГИЧЕСКИЕ УСЛОВИЯ КАК ФАКТОР РАЗВИТИЯ ЭКОЛОГИЧЕСКОГО МЫШЛЕНИЯ У СТУДЕНТОВ ПЕДАГОГИЧЕСКОГО ВУЗА - Обидова, Г.К. (SCIENCE and SOCIETY, 2017)
The article considers a wide range of environmental thinking of the young generation, taking into account the spiritual and moral values, their creative and innovative approaches. The author also studies targeted training, as well as the solution of unreasonable behavior.